Study of Microwave-Assisted MoS2 and Graphene Composite Counter Electrode for Dye-Sensitized Solar Cells - Yi, Ling; Sun, Hengchao; Yang, Wen; Chen, Weina; Luo, Jian; Wang, Jinyan; Kang, Xing; Luo, Detian; Ma, Bing; Wang, Yanjun; Su, Songyong; Wang, Zheng (Frontiers in Materials, 2021)
Graphene-MoS2 composites were synthesized via one-step microwave assisted chemical bath deposition and used as counter electrodes for dye-sensitized solar cells, instead of traditional Pt film which is high cost and poor stability. The effects of graphene additive amount on the performance of cells were studied. The results reveal that sheet porous structure graphene and MoS2 particles incorporated tightly, which is benefit of electrical conductivity and catalysis ability. A maximum efficiency of 6.3% has been achieved under 100 mW cm-2 illumination when the Mo:C is 1:1.